Effect of Counselling Services on Parental Management of Children with Cerebral Palsy in Enugu State, Nigeria - Eke, Vitalis Ugochukwu; Okeke, Stella Uchechukwu; Okon, Edet Effiong; Chukwura, Margaret Uchenna; Ushie, Godwin Beshibeshebe; Nnaji, Emeka Samuel; Offem, Odim Otu; Oko, Bernard Atrogor; Dijeh, Ann Emani; Okute, Agnes Lawrence; Onabe, Maria Bisong; Olom, Patricia Akwaya; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Cerebral palsy (CP) is a neurological disorder affecting movement, muscle tone, and posture. It is often caused by damage to the developing brain, usually before, during, or shortly after birth. The condition can have a significant emotional, physical, financial, and social impact on parents. This study investigated the effect of counseling services on the parental management of children with CP in Enugu State. Methods: A pre-test and post-test quasi-experimental design was adopted. A validated self-developed Parent of Cerebral Palsy Management Self-Report Scale (PCPMSS, r-0.78) was used for data collection. The Counseling Treatment Package (CTP) was used as the intervention in the study. Parents of children with Cerebral palsy were exposed to eight weeks of counseling sessions. The data collected were statistically analyzed using a pairwise t-test to measure the effectiveness of the intervention. One sample t-test was also used to test self-report intervention effectiveness and satisfaction with the intervention. Results: The results indicate that parents exposed to family counseling improved significantly in handling family-oriented challenges. Counseling intervention improved the emotional stability of parents of children with CP. Conclusion: It was recommended, among other things, that counseling services and other evidence-based interventions be provided for parents of children with CP to equip them with relevant coping skills and resources needed to support their children’s development.